Heat affected zone morphology of TIG torch welded HSLA steel in presence of Ti and V microalloying elements - Maleque, Md. Abdul (Elsevier, 2018)
The welding of high strength low alloy (X-65 HSLA) steels is essential for manufacturing, which inevitably affects the structural performance of the final product through the microstructure and mechanical properties of the weld joints as a result of the thermal cycles that the steel experiences during welding. In fact, there is general agreement that the morphology of heat affected zone (HAZ) have the weakest microstructure and mechanical properties relative to the rest of the steel joint and the base metal. This is mainly due to the microstructural alterations in the HAZ taking place during welding. The martensite-austenite (M-A) constituents formed in the HAZ regions predominantly govern property deterioration by promoting the initiation and propagation of the catastrophic failure. Therefore, it is necessary to find a solution to such these problems which associated with the welding operations that greatly affect the main properties of these alloys and restrict their uses. Accordingly, in this study, the aim was to evaluate the influence of welding parameters represented in heat input and the effect of Ti and V microalloying elements additions on the microstructure and microhardness in the HAZ using TIG torch welding technique on the X-65 HSLA steel. The results showed that a significant reduction in the hardness of the HAZ with the addition of Ti and V. In addition, the width of the HAZ and the grain size have been affected by these additives, this gave a positive reflection on the mechanical and microstructure properties of this critical zone of welding.